Relationship among big five personality traits, compulsive buying and variety seeking - Erciş, Aysel; Ünalan, Musa (My University, 2017)
Purpose- This study examined associations among the Big Five personality dimensions and compulsive buying tendency and variety seeking tendency in Erzurum. Methodology- Participants (n=389) completed a survey that included measures of personality, compulsive buying and variety seeking. Findings- The results revealed that four personality traits (extraversion, agreeableness, conscientiousness, and openness to experience) were positively correlated with variety seeking tendency. Extraversion was positively related with compulsive buying tendency, and conscientiousness was negatively related with CBT. Finally, compulsive buying tendency was positively related with variety seeking tendency. Conclusion- Six of eleven hypotheses are accepted in our model. Our study shows that the perception levels of participants in the way of variables, the highest-valued personality factors are agreeableness and conscientiousness, while the lowest-valued personality trait is emotional stability. The perception level of compulsive buying tendency is very low. However, the perception level of variety seeking is high.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Big five personality; Compulsive buying; Variety seeking